THE PHENOMENON OF MUSRENBANG IN TERMS OF LOCAL WISDOM: AN EFFORT TO PREVENT CORRUPTION IN THE LOCAL GOVERNMENT - Ahmad Taufiq Masbuhin; M. Nizarul Alim; Tarjo Tarjo (Asia Pacific Fraud Journal, 2018)
This study viewsthe Deliberation of Development Planningof Local Government Work Plan(Musrenbang-RKPD) process inlocal government in terms of local wisdom. This research explores the values contained in the motto “Hurub Hambangun Praja” finds out the extent to whichthe local wisdom value of “Hurub Hambangun Praja” is implemented in the Musrenbang RKPD process. The method used is qualitative with ethnography approach. In the motto “Hurub Hambangun Praja” containsthe values of willing to sacrifice, mutual cooperation, and unity in motion. Sources of data or research information are obtained from interviews, secondary data and observations with research sites in Blitar Regency. The results of this study show that the application of the values of willing to sacrifice, mutual cooperation, and unity in motionin the implementation of Musrenbang is still low.